PENGARUH CITRA MEREK, HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN MEMBELI PRODUK SEPEDA MOTOR HONDA. Studi kasus pada pemilik speda motor Honda di desa Arjasa Kecamatan Arjasa - Fajar Setia; Rois Arifin (E-JRM : Elektronik Jurnal Riset Manajemen, 2017)
AbstractThe purpose of this study is to know and analyze the effect of BrandImage, Price and product quality simultaneously and partially to the decision tobuy Honda motor case study on the owner of Honda motorcycle in Arjasa Village,Arjasa District. The sampling technique using purposive sampling is theconsideration of certain criteria. Data analysis tool used in this research isMultiple Linear Regression Analysis.Based on the results of this study note that the value of Fcount41.653>Ftable 3.11 so it can be concluded that Brand Image, Price and Productquality simultaneously influence the decision to buy a Honda motorcycle. As wellas variable Brand Image, Price and Product Quality partially influence toDecision buy Honda brand motorcycle product Case study on the owner of Hondamotorcycles in Arjasa Village District ArjasaKeywords: Brand Image, Price, Product Quality and Purchase Decision